Comparison of Graft Length Changes During Knee Motion Among 5 Different Anatomic Single-Bundle Anterior Cruciate Ligament Reconstruction Approaches: A Biomechanical Study. Issue 3 (26th March 2019) - Tanabe, Yoshie; Yasuda, Kazunori; Kondo, Eiji; Kawaguchi, Yasuyuki; Akita, Keiichi; Yagi, Tomonori
Background: In several anatomic single-bundle anterior cruciate ligament (ACL) reconstruction (ASB-ACLR) procedures, the femoral and tibial tunnel apertures are created at different locations within the native ACL attachment area. Hypothesis: Graft length changes during knee motion will be different among ASB-ACLR procedures with different femoral and tibial tunnel aperture locations. Study Design: Controlled laboratory study. Methods: A total of 12 cadaveric knees were used in this study. In each knee, 4 and 3 thin tunnels were created within the ACL attachment area on the femur and the tibia, respectively. Using 1 of 5 different combinations of femoral and tibial tunnel aperture location, 5 ASB-ACLRs were performed on each knee. In each reconstruction approach, a strong thread was used in place of the tendon graft, and the tibial graft end was tethered to a custom-made isometric positioner at 0° of knee flexion, with an approximately 12-N load applied to the thread. Then, each specimen underwent 5 cycles of knee flexion-extension motion in a range between 0° and 120°, and graft length changes were determined for each SB-ACLR approach. Results: The length changes of the graft were significantly different among the 5 ASB-ACLRs. The maximum length change values of the 3 grafts that were implanted between the femoral and tibial centers of the posterolateral bundle attachments or implanted into the femoral tunnel created at the center of the fanlike extension fiber attachment were significantly greater than those of the graft implanted between the centers of the anteromedial bundle attachments ( P < .0001) and of the graft implanted between the centers of the whole ACL attachments ( P < .0001). Conclusion: The length changes of the graft during knee motion were significantly different among the 5 ASB-ACLR approaches, even though all of the tunnel apertures were created within the femoral and tibial attachments of the native ACL. Clinical Relevance: The grafts in the first 3 graft locations may be so relaxed during knee flexion that they cannot resist anterior drawer loads exerted on the tibia.